Onion bulb vernalization period for seed production in the Northeast Brazil - Aguiar, Paulo Anselmo A. (Pesquisa Agropecuaria Brasileira, 2014)
Onion (Allium cepa L.) mother bulbs of three cultivars - Pera IPA I, Pera IPA IV, Roxa IPA III - were submitted to the artificial vernalization process in cold chamber, under 8 to 10°C during 30, 60, 90 and 120 days. It was detected that increasing the vernalization period resulted in an increase in percentage of flowering, number of seedstalk per plant and a greater seed yield. Through the regression analysis, the recommended vernalization period for each cultivar was detected, which is normally between 90 to 120 days, under the Northeast conditions of Brazil.